2011
DOI: 10.1149/1.3596376
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Phase Transformation Behavior in Li(Mn1.5Ni0.5)O4 Cathodes Studied By In Situ XRD

Abstract: In situ X-ray diffraction of Li(Mn 1.5 Ni 0.5 )O 4 was performed using a novel electrochemical cell based on coin cell hardware. The pristine material had a cubic spinel structure with a Ni 2þ oxidation state. As the cell was charged through its 4.75V plateau, a transition between spinels with Ni 2þ , Ni 3þ , and Ni 4þ oxidation was observed. As the oxidation of the nickel increased, the lattice parameter of the corresponding spinel diminished. During discharge, the spinel reversed its phase changes until only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 43 publications
4
37
1
Order By: Relevance
“…In situ XRD cells were prepared as previously described 17,18 with some modifications. The in situ XRD cell is shown in Figure 1 at various stages of fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…In situ XRD cells were prepared as previously described 17,18 with some modifications. The in situ XRD cell is shown in Figure 1 at various stages of fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…However, a different phase diagram has been reported for this same disordered LMN, with a solid solution for large values of x, followed with a two-phase region at x * 0.6, due to the onset of a second cubic phase, phase II, then another two-phase region is observed at x < 0.4, in which phase II coexists with another cubic phase, phase III [42]. Rhodes et al [35] have found that the three phases coexist in a finite range of concentrations. However, the authors did not specify if their measurements were made on ordered or disordered LMN.…”
Section: Lnm Versus Cr-doped Lnmmentioning
confidence: 78%
“…32) from dc-susceptibility measurements [30]. As an alternative approach, the off-stoichiometric material LiNi 0.5 Mn 1.5 O 4−δ has been synthesized in the disordered structure [9,[31][32][33][34][35]. The small voltage plateau at ca.…”
Section: Electron Energy In Libsmentioning
confidence: 99%
See 2 more Smart Citations